Gambaran Trauma yang Dialami Anak Korban Perceraian - M. Harwansyah Putra Sinaga; Miftahul Hasana Putri; Rohimatun Fadilah Munte; Fitri Hariani Hasibuan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This study aims to determine the types of trauma experienced by adolescents due to parental divorce and what children of divorce victims do to overcome the trauma of parental divorce. This research uses a qualitative descriptive approach with a case study type of research. Data collection was carried out by interviews and questionnaires. The data analysis technique used is the Miles and Huberman analysis model, namely data reduction, data presentation, and drawing conclusions. The results of this study explain that the impact of divorce on children depends on parents' understanding of children's feelings and the parenting style provided. However, parental divorce greatly impacts the psychology of children who will experience trauma from parental divorce, such as children who will feel lonely over parental separation, fear of building a household relationship, and hatred that comes to one of the parties that causes divorce. In dealing with the trauma experienced by children who are victims of divorce, namely by telling the problems they face to people they trust, and telling the problems, children will feel cared for and feel loved, then by motivating themselves by doing activities that help to overcome the trauma they are experiencing. Because by doing fun activities, you will forget about the problems you are facing and will accept your own situation. Keywords: Types of Trauma, Overcoming Trauma, Divorce, Trauma